Clinical study of intra-abdominal pressure in the acute surgical abdomen - Neelam, Kumari; Kumar, Amit; Singh, Vineet; Yadav, Surjeet Kumar (International Surgery Journal, 2017)
Background: Intra-abdominal pressure (IAP) is the steady-state pressure concealed within the abdominal cavity. Early recognition of rising abdominal pressure is critically important, because it allows prompt intervention which will prevent Abdominal compartment syndrome (ACS) from developing, leading to a much better prognosis for the patient. This prospective case-control study was aimed at characterisation of this entity in the commonly encountered acute surgical abdomen i.e. perforation peritonitis, intestinal obstruction and the blunt abdominal trauma. The stress was laid upon the detection of the intra-abdominal pressure in the patients and the effect of this entity upon the routinely available clinical and laboratory parameters of organ functions. The organ systems studied were the renal, cardiovascular and the pulmonary systems. The clinical outcome was also analysed. Methods: This is a prospective study conducted in Rajendra Institute of Medical Sciences, Ranchi, Jharkhand over a period of one and half year (January 2014 to June 2015). A total of 120 patients were studied, including 30 as controls. The intra-vesicular pressure was measured in all the subjects, which indirectly gives intraabdominal pressure. Results: Initial intra-abdominal pressure ranged from 0-31 cm of saline with the mean of 13.77±8.46. The mean values of the intra-abdominal pressure in the study groups i.e acute surgical cases were found to be significantly higher, as compared to that of the control group (p<0.01). Highest mortality was observed in the IAP range of >25 cm of saline (33.33%, 4 out of 12). Conclusions: Raised intraabdominal pressure significantly affects outcome and increases mortality.